An arbitrary power law device based on integrators - Kiranon, Wiwat; Loescharataramdee, Chariya; Petchakit, Wijittra; Sangpisit, Wipa (My University, 2000)
A new simple arbitrary power law device implemented from integrators along with the sample-and-hold technique is presented. The number of the integrators indicates the index of the power law. Part of the integrators determine an appropriate time interval to be used to control the sample-and-hold circuit to extract the correct output. To test the validity and value of the proposed method, numerous power law functions have been experimented. The experimental results show very close agreement with the theoretical analysis. In addition, the measurement output, possibly as large as a few volts, is obtained with extreme precision. © 2000 IEEE.
Keywords: Analog signal processing; Divider; Integrator; Multiplier; Power law device; Sample-and hold technique